LANDSCAPE IN THE WORK OF ARTISTS AND THE RELATIONSHIP OF TONE AND COLOR IN IT (Academia Science Repository, 2023)
This article consists of observing the Badi culture, life, and figurative tasting through the compassionate in the streamers, imitating Badi thought, ability, and instilling little creative activity.